An explorative study on the interaction of cyclin-dependent kinase inhibitor 2B antisense RNA 1 (CDKN2B-AS1/ANRIL) gene polymorphism with obesity on periodontitis among Norwegian adults - Natalia Petrenya; Laila A. Hopstock; Elin Hadler-Olsen; Farah Asa'ad; Lena Larsson; Gro Eirin Holde; Alexandre R Vieira; Birgitta Jönsson (Acta Odontologica Scandinavica)
Objective ANRIL is a pleiotropic gene with a strong link to periodontitis. ANRIL gene variant rs1537373 is associated with altered CDKN2B gene expression, which is linked to obesity. In this explorative, cross-sectional population-based study, we aimed to investigate the hypothesis that ANRIL (rs1537373) T>G may be associated with periodontitis through interactions, focusing on rs1537373×obesity interaction.